Panduan Akses Kredit Bagi Pedagang Mlijo ke Multifinance sebagai Dampak dari Perluasan Fungsi Multifinance oleh Otoritas Jasa Keuangan - Sunaryati Hardiani; Nanik Sisharini (Jurnal Manajemen dan Kewirausahaan, 2016)
The background of this study was based on results of previous studies in which the major problems facing traders mlijo to be able to do business continuity is the capital. With the enactment of Law no. 21 Year 2011 concerning FSA wherein Financing Agency can expand its business to finance Micro, Small and Medium Enterprises (SMEs), this is an opportunity for Mlijo traders to be able to raise capital effort from Formal Financial Institutions. Financing model for SMEs by Financing Institutions is out put of Research Phase I. While in this Phase II study focused on the preparation of  credit access guidelines  for SMEs. The purpose of this study is to develop of credit access guidelines  for SMEs which is a continuation of previous research results. Specific targets to be achieved is 1) Ease of SMEs to access credit to finance. 2) Make it easy for SMEs to find and prepare all the necessary credit requirements. 3) Ease for SMEs to determine the number of credits taken and the number of installments to be paid. The research method using descriptive research method and policy research. The unit of analysis is 1) These financial institutions in Malang 2) Mlijo traders in Malang and 3) the FSA in Malang. Excavations carried out with technical information FGD. Data were analyzed using descriptive analysis to describe the findings and policy, which involves all interested parties to devise a right credit access guidelines  for SMEs.https://doi.org/10.26905/jmdk.v4i2.500